Club Dynamite Bone Volleyball Top Serve Technique - Nur, Muhammad; Hudain, Muh Adnan; Sudirman, Sudirman (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research aims to determine the top serve techniques in the Club Dynamite Bone Volleyball Game. This research is quantitative descriptive research. The method used in this research is a survey with data collection techniques and using a judgment test. The population in this study were all Club Dynamite athletes. The sampling technique used total sampling, so the number of samples in this study was 15 Club Dynamite people. Data analysis uses quantitative description with percentages. The data from the overall results of this research shows that the top service technique analysis in the Bone Regency Club Dynamite Volleyball Game is in the "Enough" category